2011
DOI: 10.1021/jf104681p
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycan Profiling of Mature Human Milk by High-Performance Microfluidic Chip Liquid Chromatography Time-of-Flight Tandem Mass Spectrometry

Abstract: N-linked glycans of skim human milk proteins were determined for three mothers. N-linked glycans are linked to immune defense, cell growth, and cell-cell adhesion, but their functions in human milk are undetermined. Protein-bound N-linked glycans were released with Peptidyl N-glycosidase F (PNGase F), enriched by graphitized carbon chromatography and analyzed with Chip-TOF MS. To be defined as N-glycans, compounds were required, in all three procedural replicates, to match, within 6 ppm, against a theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 59 publications
2
53
0
1
Order By: Relevance
“…Data analysis revealed that goat milk lactoferrin N ‐glycans contained NeuAc or NeuGc. Both NeuAc‐ and NeuGc‐containing N ‐glycans are present in bovine milk proteins, but NeuGc‐containing N ‐glycans are not present in human milk proteins . In some instances, accurate mass alone is not sufficient to positively identify N ‐glycan compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis revealed that goat milk lactoferrin N ‐glycans contained NeuAc or NeuGc. Both NeuAc‐ and NeuGc‐containing N ‐glycans are present in bovine milk proteins, but NeuGc‐containing N ‐glycans are not present in human milk proteins . In some instances, accurate mass alone is not sufficient to positively identify N ‐glycan compositions.…”
Section: Resultsmentioning
confidence: 99%
“…1); and (c) the hybrid type, which consists of a mixture of these two types. The human milk Nglycome has been recently described in detail, and in general human milk N-glycans are largely fucosylated and present in larger concentrations compared to bovine milk (Dallas et al, 2011;Nwosu et al, 2012). In contrast, bovine N-glycans are also more sialylated and characterized by the presence of N-glycolylneuraminic acid (NeuGc) instead of N-acetylneuraminic acid (Nwosu et al, 2012).…”
Section: Human Milk Glycoproteinsmentioning
confidence: 99%
“…This combination demonstrated that several glycans were differentially present in the different states of health. LC chips with graphite packings are also available and have been used to characterize human milk oligosaccharides (118-120), milk carbohydrates from different primates (121), and glycans present on serum glycoproteins (122). Nearly 200 structures were identified from their exact masses in human serum; these structures included isomeric analytes (123), which were then used to construct a library based on m/z values and retention times to quickly determine the structure of a given glycan.…”
Section: Separations In Glycomicsmentioning
confidence: 99%